The Chinese calligraphy stone gallery / Xie Yingying - Xie , Yingying (2020)
This dissertation studies the reshaping of cultural memory in helping to increase cultural self-confidence and to gain cultural identity. Nirvana Group placed great emphasis on promoting Chinese culture and on the basis of respecting culture; it has established the Chinese Calligraphy Stone gallery. This dissertation found that the Chinese Calligraphy Stone gallery which is specially constructed through the installation of represented structures of China showcased the Confucian principles and Taoist thought. Cultural memory has been reconstructed based on the permanent collection of diachronic masterpieces of the elite culture of calligraphy tradition. I would like to say that the spirit of Confucianism has been stored, the concept of combining Confucianism with business has been shaped that it has a long history. Through the establishment of Chinese Calligraphy Stone Gallery, the roots of Confucian classics are recreated and thus reproducing the interpretation and practice of the Nanyang Chinese of the Confucian’s merchant spirit. Therefore, has constructed a long history of Confucian merchants’ cultural memory.